Legal Liability of Labour Recruitment Agencies in Ensuring The Rights of Indonesian Women Migrant Workers Abroad - Asyikin, Marsya; Jaya, Febri; Nurlaily, Nurlaily (Sean Institute, 2026)
The international mobility of Indonesian women migrant workers constitutes a global phenomenon that is closely associated with a high risk of human rights violations, particularly due to inadequate legal protection during both the placement process and the period of employment. Labour recruitment agencies play a strategic role as key actors responsible for ensuring the fulfilment of women migrant workers’ rights from the pre-departure stage through placement and post-placement phases. This study aims to analyse the legal framework and the implementation of the legal responsibilities of labour recruitment agencies in guaranteeing the rights of Indonesian women migrant workers employed overseas. This research adopts an empirical legal research method, employing an integrative approach that combines a statutory analysis of key regulations particularly Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers with a sociological approach to examine the institutional behaviour of labour recruitment agencies in carrying out their legal obligations. The findings indicate that although Law Number 18 of 2017 normatively provides comprehensive regulations regarding the duties and responsibilities of labour recruitment agencies, its implementation in practice remains suboptimal. The primary weaknesses are found in legal education for workers, assistance during the placement period, monitoring systems, and post-contract protection mechanisms, which tend to be administrative in nature and insufficiently oriented towards rights restoration. Therefore, this study recommends strengthening state supervision, integrating inter-agency protection systems, and reinforcing the accountability of labour recruitment agencies as agents of legal and social protection in order to achieve fair, humane, and sustainable protection for women migrant workers.